Inhibition of Rothia Species by Over-the-Counter Products and Bacterial Antagonists - Mark, Cannon L; B, Kabat; R, Yogev; L, Jantra; A, Awan; C, Le; K, White; A, Vorachek (Edelweiss Applied Science and Technology, 2020)
The interaction between the human host micro biome and over the counter products has recently been investigated, with surprising results. Some over the counter items may negatively affect the health of the host, supporting the concept of the “hygiene hypothesis”, that is, that disease may be actually caused by the lack of beneficial commensal bacteria. Recent reports on the gluten metabolizing genus, Rothia, and a possible association with Celiac Disease beg the question, what happened to the Rothia? In this study inhibitory factors, such as, Over The Counter oral hygiene products and antagonistic bacteria were investigated and, in vitro, significantly inhibited the gluten metabolizing bacteria, possibly affecting human digestion and contributing to gluten sensitivity.